CULTIVATING SHARED WEALTH: THE IMPACT OF REGIONAL UNIVERSITIES ON LOCAL ECONOMIC GROWTH - Mendez , Sara (Ayden International Journal of Education and Social sciences, 2024)
The pursuit of common prosperity is a central objective outlined in the Fifth Plenary Session of the 19th Central Committee of the Communist Party of China (CPC). It is not merely an economic endeavor but a crucial political imperative linked to the Party's governance foundation. Zhejiang Province's release of the "Implementation Plan for Zhejiang's High-Quality Development and Construction of Common Wealth Demonstration Area (2021-2025)" underscores the significance of this pursuit, reinforcing its multidimensional importance in both economic and political domains. This context necessitates the active involvement of local universities in aligning with this overarching mission, seizing the opportunity to contribute to regional economic development, and facilitating the realization of common prosperity. In the current era, higher education assumes a pivotal role as an internal catalyst for common prosperity and represents a significant dimension of its attainment.